A comparative study of scopolamine, D-Galactose and AlCl3-induced Alzheimer’s like disease by enhancing hippocampal neurodegeneration and memory impairment in male rats - Bnar Rasul Abdulrahman ,Zana Rafiq Majeed (Zanco Journal of Pure and Applied Sciences, 2023)
Alzheimer’s disease (AD) is a debilitating neurodegenerative disorder identified by progressive loss of neurons, cognition decline, and memory deficits. The current study sought out to compare the effects of scopolamine (SCO), D-galactose (D-gala), and aluminium chloride (AlCl3) on memory performance, histological alterations of the hippocampus, and to determine the best model for inducing Alzheimer’s-like disease. Twenty-four male adult albino rats (250–300g) were used in this study, which were arbitrarily assigned into four groups: control group (normal saline), SCO group (2 mg/kg), D-gala group (125 mg/kg) and AlCl3 group (50 mg/kg). The chemicals were given intraperitoneally for 30 days. All the rats were subjected to novel object recognition (NOR) and Barnes maze (BM) tests to assess memory performance. At the end of the period, all the rats were anesthetized, blood samples were taken for hematological and biochemical tests, and the brains were removed for morphometric analysis. The results have demonstrated that SCO, D-gala, and AlCl3 caused memory impairment in BM and NOR tests, and malondialdehyde (MDA) serum levels significantly increased. Histological analysis showed degenerative pyknotic cells in the rat hippocampus. The impairment in memory performance and histopathological alterations were higher in the AlCl3 than in the other models, but the hematological parameters were significantly changed. Therefore, it was concluded that SCO (2 mg/kg) is the best model for mimicking AD-like disease among D-gala and AlCl3 by enhancing histopathological alternations and declining memory in rats without affecting other study parameters.